2021
DOI: 10.3390/ma15010260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Corrosion Behavior of Friction-Stir-Welded Dissimilar Aluminum Alloys

Abstract: The fuel consumption of high-density automobiles has increased in recent years. Aluminum (Al) alloy is a suitable material for weight reduction in vehicles with high ductility and low weight. To address environmental problems in aircraft and maritime applications, in particular rust development and corrosion, the current study assesses the corrosion behavior during friction stir welding (FSW) of two dissimilar Al alloys (AA6061 and AA8011) in various corrosive conditions using salt spraying and submersion test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The findings of the microstructural evaluation of the corroded surfaces are in line with the findings of Santhosh N et al, who have reported that the formation of the oxide films on the aluminium suface inhibits further corrosion due to the passivation of the surface layer towards the catalytic reactions [16]. Further, the works of Ramesha K et al, on the corrosion of the friction stir weld surfaces have reiterated the fact that the secondary processing operations brings about microcoring and segreggation that inibits the subgranular pitting reaction and thereby reduces the rate of corrosion [17]. Rami Alfattani et al, have further studied the corrosion behaviour of the friction stir weld specimens and have revealed that the microstructural refinement at the weld zone exhibits better corrosion resistance than the base metal, due to the zonal refinement and better bonding between the atoms leading to the reduction in the crevices and imperfections, thereby reducing the corrosion at the interface [18].…”
Section: (1)supporting
confidence: 76%
“…The findings of the microstructural evaluation of the corroded surfaces are in line with the findings of Santhosh N et al, who have reported that the formation of the oxide films on the aluminium suface inhibits further corrosion due to the passivation of the surface layer towards the catalytic reactions [16]. Further, the works of Ramesha K et al, on the corrosion of the friction stir weld surfaces have reiterated the fact that the secondary processing operations brings about microcoring and segreggation that inibits the subgranular pitting reaction and thereby reduces the rate of corrosion [17]. Rami Alfattani et al, have further studied the corrosion behaviour of the friction stir weld specimens and have revealed that the microstructural refinement at the weld zone exhibits better corrosion resistance than the base metal, due to the zonal refinement and better bonding between the atoms leading to the reduction in the crevices and imperfections, thereby reducing the corrosion at the interface [18].…”
Section: (1)supporting
confidence: 76%
“…They also found that galvanic coupling caused high corrosion density at the nugget zone. Out of all samples, less corrosion resistance was obtained for the sample welded at high rotation speed due to the formation of defects and insufficient material mixing [30][31][32].…”
Section: Open Circuit Potential (Ocp) Testmentioning
confidence: 99%
“…Therefore, numerous solutions have been proposed to reduce fuel consumption and minimize the damage to the environment [2,3]. These solutions include reducing the weight of vehicles and promoting the use of lightweight alloys [4]. Magnesium (Mg), which is a lightweight metal, has drawn attention due to its property of being the lightest structural metal [5,6].…”
Section: Introductionmentioning
confidence: 99%